PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Bongsu Saragih (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
Bastard Clothing is a home industry that is also used as a brand or brand T-shirt distro that began to appear in early 2015. Promotion of the right target and good product quality greatly affect the community (consumers) in making the purchase of these products. Product quality greatly affects consumer purchasing decisions on a product, a good product in terms of quality or price will not be easy to compete if it is wrong in doing promotional activities. This study aims to analyze the contribution of simultaneous between product quality and promotion to purchase decision, analyze the partial contribution between product quality to a decision of purchasing and analyze the contribution of partially between promotion to purchasing. Samples in this research counted 44 respondents. The analysis technique used multiple regression analysis. The results of the analysis show that promotion and product quality simultaneously have a significant contribution on purchasing decisions, which means that the more attractive promotions made by companies and products offered quality can improve purchasing decisions. Product quality affects purchasing decisions, it indicates that the more quality products offered to consumers can improve purchasing decisions. Promotion contribution purchasing decisions, indicating that the more companies promotion can improve purchasing decisions.